2022
DOI: 10.1186/s41983-022-00563-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and monkeypox: what is common and what is not in a present pandemic versus a potential one—a neuropsychiatric narrative review

Abstract: Pandemic represents challenging medical emergency as it is usually associated with high rates of mortalities and morbidities. Along the last 2 and half years the world has faced the emergence of severe acute respiratory syndrome corona virus 2 pandemic that caught medical agencies and health authorities by surprise and costed more than half billion morbidities and 6 million mortalities. Unfortunately, the way developed countries contained the novel corona virus was unsatisfactory in means of early quarantines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The most important conclusion about this value which affects the population is that the infection of the 2022 human MPOX disease starts to spread, that is, the 2022 human MPOX disease is a pandemic in its 2022 outbreak. This can be compared with the previous problem, which is the 2019 coronavirus disease 19 , 50 53 where it is seen that the spreading rhythm of the 2022 human MPOX disease is less than that of the 2019 coronavirus disease. Also, it is found that the values of herd immunity for the 2022 human MPOX disease are 35.52% for the United States and 30.99% for Spain.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The most important conclusion about this value which affects the population is that the infection of the 2022 human MPOX disease starts to spread, that is, the 2022 human MPOX disease is a pandemic in its 2022 outbreak. This can be compared with the previous problem, which is the 2019 coronavirus disease 19 , 50 53 where it is seen that the spreading rhythm of the 2022 human MPOX disease is less than that of the 2019 coronavirus disease. Also, it is found that the values of herd immunity for the 2022 human MPOX disease are 35.52% for the United States and 30.99% for Spain.…”
Section: Discussionmentioning
confidence: 96%
“…Also, a study discussed the detection of traces of the disease in clinical samples 18 . Some studies showed specific reviews about the MPOX disease in 2022 or compared with other diseases 19 , 20 . The 2022 outbreak of the human MPOX disease began to spread over 111 countries around the world (including the suspected cases) as of the middle of December 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Although SARS-CoV-2 and MPXV are both enveloped viruses that replicate in the cytoplasm and require host machinery to replicate and make new viral proteins, there are distinctions between the two viruses [ 23 ]. MPXV is a double-stranded DNA virus, whereas SARS-CoV-2 is a single-stranded RNA virus.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the possible relationship between monkeypox and COVID-19. One connection is that patients with SARS-CoV-2 infection are more prone to coinfect with MPXV due to the reduced amount of circulating immune cells [ 23 ]. Another link between the SARS-CoV-2 and MPXV outbreaks is a lack of immunity in younger generations to the smallpox virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation